Detection of Brain Somatic Mutations in Cerebrospinal Fluid from Refractory Epilepsy Patients. Issue 6 (20th April 2021) - Kim, Seyeon; Baldassari, Sara; Sim, Nam Suk; Chipaux, Mathilde; Dorfmüller, Georg; Kim, Dong Seok; Chang, Won Seok; Taly, Valérie; Lee, Jeong Ho; Baulac, Stéphanie
Abstract : Brain mosaic mutations are a major cause of refractory focal epilepsies with cortical malformations such as focal cortical dysplasia, hemimegalencephaly, malformation of cortical development with oligodendroglial hyperplasia in epilepsy, and ganglioglioma. Here, we collected cerebrospinal fluid (CSF) during epilepsy surgery to search for somatic variants in cell‐free DNA (cfDNA) using targeted droplet digital polymerase chain reaction. In 3 of 12 epileptic patients with known somatic mutations previously identified in brain tissue, we here provide evidence that brain mosaicism can be detected in the CSF‐derived cfDNA. These findings suggest future opportunities for detecting the mutant allele driving epilepsy in CSF. ANN NEUROL 2021;89:1248–1252